Chemistry and Antifungal Activity of Homoisoflavonoids - Alana R. Ferreira; Damião P. de Sousa (Journal of Chemistry)
This review deals with the antifungal profile of a subclass of natural products known as homoisoflavonoids. These molecules belong to the larger flavonoids class, yet they are less common for presenting an extra carbon in their basic chemical structures. Homoisoflavonoids are important bioactive molecules because they exhibit promising antimutagenic, antiproliferative, antioxidant, anti-inflammatory, and antimicrobial activity. This review lists the principal experimental studies addressing homoisoflavonoid antifungal activity with the aim of discussing the role of these molecules in obtaining new antifungal agents. The vast majority of research consists of antimicrobial screenings. It was noted that sappanin-type homoisoflavonoids commonly exhibit antifungal activity, but their overall antifungal profile is still very little known. Studies evaluating mechanisms of action are needed to better understand the antifungal potential of homoisoflavonoids.